Interethnic marriage: a choice between ethnic and educational similarities - Delia Furtado; Nikolaos Theodoropoulos (Institute for the Study of Labor (IZA), 2008)
This paper examines the effects of education on intermarriage, and specifically whether the mechanisms through which education affects intermarriage differ by immigrant generation, age at arrival, and race. We consider three main paths through which education affects marriage choice. First, educated people may be better able to adapt to different cultures making them more likely to marry outside of their ethnicity (cultural adaptability effect). Second, because the educated are less likely to reside in ethnic enclaves, meeting potential spouses of the same ethnicity may be difficult (enclave effect). Lastly, if spouse-searchers value similarities in education as well as similarities in ethnicity, then the effect of education will depend on the availability of same-ethnicity potential spouses with a similar level of education (assortative matching effect). Using data from the 2000 U.S. Census, we find that controlling for the enclave effect, there is empirical evidence for both the cultural adaptability and assortative matching effects. Our estimates also suggest that assortative matching is relatively more important for the native born rather than the foreign born, for the foreign born that arrived young rather than old, and for Asians rather than Hispanics. We provide additional evidence suggestive of our hypotheses and discuss policy implications.
urn:nbn:de:101:1-2008042124
Keywords: J12; 300; Ethnic intermarriage; education; immigration; Ehe; Migranten; Ethnische Beziehungen; Bildungsniveau; USA